Case report: A fatal case of myocardial infarction due to myocardial bridge and concomitant vasospasm: the role of stress gated SPECT - Oh, Seok; Hyun, Dae Young; Cho, Sang-Geon; Hong, Young Joon; Kim, Ju Han; Ahn, Youngkeun; Jeong, Myung Ho (Frontiers in Cardiovascular Medicine, 2023)
Introduction Although most cases of myocardial bridge (MB) are clinically benign, sometimes it can be one of potential threats of myocardial infarction (MI) and life-threatening arrhythmia. In the present study, we present a case of ST-segment elevation MI caused by MB and concomitant vasospasm. Case Presentation A 52-year-old woman was brought to our tertiary hospital due to resuscitated cardiac arrest. Because the 12-lead electrocardiogram indicated ST-segment elevation MI, coronary angiogram was promptly commenced, which showed near-total occlusion at the middle portion of left anterior descending coronary artery (LAD). After intracoronary nitroglycerin administration, this occlusion was dramatically relieved, however, systolic compression at this site remained, indicative of myocardial bridge (MB). Intravascular ultrasound also showed eccentric compression with a “half-moon” sign, which is consistent with MB. Coronary computed tomography also showed a bridged coronary segment surrounded by myocardium at the middle portion of LAD. To assess the severity and extent of myocardial damages and ischemia, myocardial single photon emission computed tomography (SPECT) was additionally conducted, showing a moderate fixed perfusion defect around the cardiac apex, suggesting MI. After receiving optimal medical therapy, the patient's clinical symptoms and signs were improved then the patient was discharged from the hospital successfully and uneventfully. Conclusion We demonstrated a case of MB-induced ST-segment elevation MI which was confirmed with its perfusion defects via myocardial perfusion SPECT. There have been proposed a number of diagnostic modalities to examine its anatomic and physiologic significance. Among them, myocardial perfusion SPECT can be available as one of useful modalities to evaluate the severity and extent of myocardial ischemia in patients with MB.